Varietal diversification for enhanced productivity and profitability under diverse production systems - PATEL, SHASHANK; RATHORE, S S; SHEKHAWAT, KAPILA; JANGIR, RAMETI; SINGH, R K; BABU, SUBHASH; IQBAL, MOH (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted during rabi 2020– 21 to study the effect of different production systems on yield and economics of mustard varieties. The seed yield of mustard crop was significantly high under ICM (2259.0 kg/ha), while maximum stover (7950 kg/ ha) and biological yield (9936 kg/ha) was recorded under CA. Among the mustard varieties, PM 26 resulted in significantly higher seed (2206 kg/ha), stover (8505 kg/ha) and biological yield (10711 kg/ha). ICM gave maximum net returns of `76583/ha, while with respect to variety, PM 26 gave maximum net returns of `76060/ha. CA and CS resulted in higher B:C ratio (3.3 and 3.12, respectively) compared to OMS and ICM, while among the varieties maximum B:C ratio was recorded from PM 26 (3.22). Different production systems under different mustard varieties showed the positive impact on crop productivity as well as on economics. The varietal diversification of maize based system with Pusa mustard 26 and Pusa mustard 28 Indian mustard varieties gave maximum productivity, profitability under integrated crop management system.